2012
DOI: 10.1038/cr.2012.180
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-29b is a novel mediator of Sox2 function in the regulation of somatic cell reprogramming

Abstract: Fibroblasts can be reprogrammed into induced pluripotent stem cells (iPSCs) by the application of Yamanaka factors (OSKM), but the mechanisms underlying this reprogramming remain poorly understood. Here, we report that Sox2 directly regulates endogenous microRNA-29b (miR-29b) expression during iPSC generation and that miR-29b expression is required for OSKM-and OSK-mediated reprogramming. Mechanistic studies show that Dnmt3a and Dnmt3b are in vivo targets of miR-29b and that Dnmt3a and Dnmt3b expression is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 45 publications
4
73
1
Order By: Relevance
“…The expression of endogenous miRNAs is regulated by transcription factors [160] . The expression of miR-29b is directly regulated by Sox2 during iPSC generation and miR-29b is an essential facilitator for Oct4, Klf4, Sox2, and c-Myc (or Oct4, Klf4, and Sox2) mediated reprogramming [161] . Reported reprogramming factors Oct4, Klf4, Sox2, and c-Myc have demonstrated that miRNAs play a crucial role in regulating stem cell fate events, such as reprogramming, differentiation, and self-renewal.…”
Section: Micrornas In Reprogrammingmentioning
confidence: 99%
“…The expression of endogenous miRNAs is regulated by transcription factors [160] . The expression of miR-29b is directly regulated by Sox2 during iPSC generation and miR-29b is an essential facilitator for Oct4, Klf4, Sox2, and c-Myc (or Oct4, Klf4, and Sox2) mediated reprogramming [161] . Reported reprogramming factors Oct4, Klf4, Sox2, and c-Myc have demonstrated that miRNAs play a crucial role in regulating stem cell fate events, such as reprogramming, differentiation, and self-renewal.…”
Section: Micrornas In Reprogrammingmentioning
confidence: 99%
“…LincRNA-p21 was predominantly nuclear ( Figure 3A), consistent with a potential role in epigenetic regulation. Then, we employed RNA immunoprecipitation (RIP) with antibodies against a panel of chromatin modifiers detrimental for reprogramming [9][10][11][12]23] using lysates from MEFs reprogrammed with OSKM on day 12. Notably, there was a substantial enrichment for lincRNA-p21 in DNMT1 RIP and a less substantial enrichment in SETDB1 RIP, but no enrichment in DN-MT3A/B and SUV39H1 RIPs, relative to IgG control ( Figure 3B).…”
Section: Lincrna-p21 Associates With Setdb1 and Dnmt1 In Separate Repmentioning
confidence: 99%
“…19 The miR-29 family is also more broadly relevant to stem cell biology, as miR-29b recently was shown to be upregulated by Sox2 and required for reprogramming of fibroblasts into induced pluripotent stem cells. 20 Although little is known about how miR-29a transcript levels are regulated, CCAAT/enhancer-binding protein alpha (CEBPA) has been reported to positively regulate the miR-29a/b-1 cluster and expression of miR-29a/b is suppressed in acute myeloid leukemia (AML) patients with impaired CEBPA function. 21 To understand the physiologic role of miR-29a in normal hematopoietic development, we evaluated HSPCs in mice harboring a genetic deletion of the miR-29a/b-1 bicistron.…”
Section: Introductionmentioning
confidence: 99%